An Empirical Performance Evaluation of Open-end Funds in China - ZHANG, JING (2009)
In recent years, securities investment funds are developing dramatically in China, either in terms of size or variety. The China‘s fund industry as the largest emerging market in the world has successful drawn global investors‘ attention, although the financial mechanism and market efficiency in China is still not mature enough. Currently, the investment funds in China played an important role in economic stable development of the capital market. It thus made the demand increase for the evaluation of the fund performance. This empirical research evaluated 26 open-end funds which carried on at least three years during the period July 2004 to June 2009. The aim of this paper include two aspects: first, examining the performance of sample funds and trying to find whether the open-end funds outperform the market benchmark. Three classical and traditional performance measures were used in this paper, including: Treynor‘s index, Sharpe‘s index, and Jensen‘s alpha. In addition, one-sample t-test was also conducted to estimate the mean difference between the open-end funds and market benchmark; second, attempting to find whether the fund‘s managers have the ability of selectivity and market timing. The T-M model and H-M model were employed to evaluate them. These research models were all based on three basic investment theories: Modern Portfolio Theory, Efficient Market Hypothesis, in particular, Capital Asset Pricing Model which widely used by many researchers. However, in many previous empirical studies, CAPM model was demonstrated is not an accurate tool in reality. That also did cause certain limitation in this dissertation.